Comparison of Onlay Mesh Repair Vs Sublay Mesh Repair for Ventral Abdominal Hernias: A Focus on Post Op Seroma Formation - Fahim Liaqat; Muhammad Qasim Butt; Usman Ghani; Mansoor Tariq Azeem; Muhammad Shoaib Khan; Tayyaba Mushtaq Khan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the effectiveness of Onlay mesh repair versus Sublay mesh repair for ventral abdominal hernias in terms of post op seroma formation. Study Design: Quasi-experimental study. Place and Duration of Study: Department of General Surgery, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Feb to Sep 2020. Methodolgy: A total of 140 patients (70 in each group) of ventral abdominal hernia who met the inclusion and exclusion criteria were included in the study. Patients with complicated or recurrent hernias were excluded. Group-A patients underwent Onlay hernioplasty while in group B hernioplasty was performed via Sublay technique. All patients were followed for post op seroma formation till 2 weeks via ultrasonography. Data was analyzed by Statistical Package for Social Sciences version 22. Results: Mean operation time in Group-A was 52.30±6.65 minutes while in Group-B the mean operation time was 85.82±8.26 minutes. Post op seroma formation between the two groups was 18.10% vs 4.65%, which was statistically significant (p=0.023). Conclusion: The occurrence of Post op seroma formation is less in Sublay lay mesh repair as compare to Onlay mesh repair however it requires longer operative time.